Tracking Poverty over Time in the Absence of Comparable Consumption Data - Stifel, David; Christiaensen, Luc (World Bank, Washington, DC, 2012)
Following the endorsement of the Millennium Development Goals, there is an increasing demand for methods to track poverty regularly. This paper develops an economically intuitive and inexpensive methodology to do so in the absence of regular, comparable data on household consumption. The minimum data requirements for the methodology are the availability of a household budget survey and a series of surveys with a comparable set of asset data also contained in the budget survey. The methodology is illustrated using a series of Demographic Health Surveys from Kenya.